Pengembangan Web Promosi UMKM Kerajinan Rajut Berbasis CMS E-Shop sebagai Solusi di Kecamatan X Koto - Wira Yudha, Gerli; Annas, Firdaus; Firdaus, Raihan (JOVISHE : Journal of Visionary Sharia Economy, 2023)
The online promotion strategy for UKM Rumah Rajut Syafir aims to enhance competitiveness and expand market reach through the development of a CMS-based E-Shop using OpenCart, which is practical and beginner-friendly. Highlight the urgent need for innovation in digital marketing. Additionally, the low interest of the local community in knitted products—due to their ability to create similar items—and the lack of exposure in broader markets further emphasize the necessity of a digital solution. This research adopts the Research and Development (R&D) method with the Waterfall development model to design a web-based promotional platform through OpenCart, ensuring its validity, practicality, efficiency, and effectiveness in supporting product marketing. The contribution of this study extends beyond the local aspect by helping UKMs improve competitiveness and expand their markets; it also has global implications by providing a digitalization model for SMEs in the handicraft industry. The research findings indicate that web-based applications like OpenCart can serve as a valuable support tool to enhance product visibility, reach more customers, and strengthen the competitiveness of home industries in the digital era. Simultaneously, they play a role in preserving local culture through knitted products, which hold artistic value and unique identity in the global trade landscape.